2012
DOI: 10.1016/j.phrp.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Evidence of Occupational Exposure to Chemicals and Other Factors among Auto-Repair Workers in Rawalpindi, Pakistan

Abstract: ObjectivesOccupational exposure to aromatic solvents causes many serious health hazards to workers, especially if an ambient environment increases the exposure during routine working hours. This study was conducted on two related groups, i.e., automobile mechanics (MCs) and automobile spray painters (PNs), with an effort to analyze effects of chemical exposure on hematological parameters, keeping a focus on environmental parameters and workers’ personal behavioral characteristics that could be held responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 36 publications
5
31
0
Order By: Relevance
“…The observed decrease in haemoglobin level of auto-mechanics is in correlation with previous studies [11] but differs from the report on oil works where the values for haemoglobin and haematocrit remained insignificant difference (P>0.05) between both groups [8]. Our findings also collaborate with the assertion that the length of exposure to petroleum pollutants correlates with adverse effect on haematological physio-chemistry [4,8,[44][45].…”
Section: Discussionsupporting
confidence: 86%
“…The observed decrease in haemoglobin level of auto-mechanics is in correlation with previous studies [11] but differs from the report on oil works where the values for haemoglobin and haematocrit remained insignificant difference (P>0.05) between both groups [8]. Our findings also collaborate with the assertion that the length of exposure to petroleum pollutants correlates with adverse effect on haematological physio-chemistry [4,8,[44][45].…”
Section: Discussionsupporting
confidence: 86%
“…Automobile manufacturing, repair stations, spray painting and other related workplaces are examples of automobilerelated occupations in Pakistan where workers face exposure to organic solvents to a great extent [1][2][3]. Among many environmental sources, benzene mostly arises from fuel vapors and gasoline which are used for degreasing and diluents at automobile mechanic work areas [4].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that it appeared that PSA were more at risk compared to auto mechanics and may develop anaemia over time. [9,10] The above effects have been attributed to the cytotoxic effects of aromatic hydrocarbons on haematopoetic precursors in the bone marrow. [11] Long term occupational exposure has been linked with a number of haematological disorders such as leukaemia, myelodysplasia and aplastic anaemia.…”
mentioning
confidence: 99%